Longitudinal Data Modeling on Physical Fitness, Organizational Activity, Gender, and its Effect on Student Grade Point Average (GPA) - Lazuardy, Ardyan; Anavisha, Jihan; Aflah, Nawal Zuhdaniel; Rachmawati, Ro’fah Nur (MUNISI: Military Mathematics and Natural Sciences, 2023)
GPA is a characteristic measurement which indicates the academic achievements of students in completing the courses in every semester. The conducted research is to determine whether the impact of various factor contribute to the student GPA with different backgrounds. Sample students and data are collected from one study program: GPA, gender, physical fitness assessment, and their organization role. The data is then represented in longitudinal model with data analysis using RStudio. The results are: first, non-random effect model showed that time variable is not significant to the GPA although there is indication of reduction. Second, random effect model of ID (student) showed time is significant to GPA with negative effect. Third, with random effect parameter of gender, it was shown that time variable is not significant to the GPA with negative effect. Fourth, with random effect ID and gender, time is greatly impacted to the GPA with negative effect. Fifth, the model with covariate variable of physical fitness shown no significant effect to the GPA, nevertheless, there is a negative effect. Sixth, covariate variable model of student engaged in corps regiment showed that there is no significant effect to the GPA but, there is a decrease of it.